EU Foreign Investment Policy: FDI Screening Mechanism to Advert Genuine Threats or Introducing Hidden Protectionism - Oplotnik, Zan Jan (2021)
For decades foreign direct investments (FDI) were privilege of companies from advanced economies, which invested in less developed economies and harvesting benefits of such activities. Leading position in capital, technology, managerial skills, etc, allowed them to penetrate markets of high potential but with less skills and lower costs (labour, raw material, etc) and standards (environmental, labour, etc.). Although USA and EU are still the far most advanced economies, adding majority of FDI to world stock and flow, since 2010, China is speeding up more than ever, investing in developed and non-developed eonomies. Only in Europe, Chinese companies invested more than 30 billion euros yearly in period from 2016 to 2018, comparing only 2 billion in 2010. That trend rised some concerns about Chinese nature of FDI, especially due to some of their peculiarities, noticed by schoolars, politiciant and domestic companies. In 2019 the EU issues Regulation (EU) 2019/452 that provides a framework for the screening of foreign direct investments and for cooperation.